2022
DOI: 10.1126/sciadv.abl5621
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic lncRNAs alter epigenetic memory at a fragile chromosomal site in human cancer cells

Abstract: Chromosome instability is a critical event in cancer progression. Histone H3 variant CENP-A plays a fundamental role in defining centromere identity, structure, and function but is innately overexpressed in several types of solid cancers. In the cancer background, excess CENP-A is deposited ectopically on chromosome arms, including 8q24/ cMYC locus, by invading transcription-coupled H3.3 chaperone pathways. Up-regulation of lncRNAs in many cancers correlates with poor prognosis and recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 85 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…Collectively these studies suggest a provocative, testable link between non-coding RNA, DNA methylation, altered gene expression and cancer progression. For example, we recently showed that when lncRNA PCAT2 gene is introduced to a naïve chromosome locus it acts in cis to mislocalize centromeric specific histone variant, thus altering the epigenetic memory and chromatin structure at the locus from where it was transcribed ( Arunkumar et al, 2022 ). LncRNAs can also interact with DNA to form RNA–DNA hybrids such as R-loops, to modulate chromatin architecture and accessibility of the transcription machinery to the underlying DNA.…”
Section: Genome Integrity and Senescencementioning
confidence: 99%
“…Collectively these studies suggest a provocative, testable link between non-coding RNA, DNA methylation, altered gene expression and cancer progression. For example, we recently showed that when lncRNA PCAT2 gene is introduced to a naïve chromosome locus it acts in cis to mislocalize centromeric specific histone variant, thus altering the epigenetic memory and chromatin structure at the locus from where it was transcribed ( Arunkumar et al, 2022 ). LncRNAs can also interact with DNA to form RNA–DNA hybrids such as R-loops, to modulate chromatin architecture and accessibility of the transcription machinery to the underlying DNA.…”
Section: Genome Integrity and Senescencementioning
confidence: 99%
“…Many lncRNAs function in regulating epigenetic modifications, some of which are also involved in the establishment of persistent epigenetic memory ( Arunkumar et al, 2022 ; Begolli et al, 2019 ; Fok et al, 2018 ; Wei et al, 2017 ). For example, recent work showed that transcription of locus 8q24-derived oncogenic lncRNAs such as PCAT2 could recruit centromeric protein-A (CENP-A), a variant of Histone H3, promote the ectopic localization of CENP-A, and alter epigenetic memory at a fragile chromosomal site in human cancer cells ( Arunkumar et al, 2022 ). In the current study, we investigated whether HOTAIR -mediated epigenetic alterations participate in enacting long-term epigenetic memory using transgenic iHOT + tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many lncRNAs function in regulating epigenetic modifications, some of which are also involved in the establishment of persistent epigenetic memory (Arunkumar et al, 2022; Begolli et al, 2019; Fok et al, 2019; Wei et al, 2017). For example, recent work showed that transcription of locus 8q24-derived oncogenic lncRNAs such as PCAT2 could recruit centromeric protein-A (CENP-A), a variant of Histone H3, promote the ectopic localization of CENP-A; and alter epigenetic memory at a fragile chromosomal site in human cancer cells (Arunkumar et al, 2022). In the current study, we investigated whether HOTAIR-mediated epigenetic alterations participate in enacting long-term epigenetic memory using transgenic iHOT + tumor cells.…”
Section: Discussionmentioning
confidence: 99%